PROFESSIONAL DEVELOPMENT OF PHYSICAL EDUCATION FACULTY IN MULTIDISCIPLINRY INSTITUTIONS OF HIGHER EDUCATION: PHILOSOPHICAL DIMENSION - Mukan, Nataliya; Zagura, Fedir (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the research of the problem of physical education faculty’ professional development in multidisciplinary institutions of higher education in the context of philosophy. The aim of the article is to single out the specifics of physical education faculty’ professional development in multidisciplinary institutions of higher education in the philosophical dimension. To achieve the aim of the study, the theoretical research methods were used: analysis and synthesis for processing scientific literature; generalization and systematization for processing the received data and formulating conclusions. The professional development of specialists is considered from the perspective of progressivism, existentialism, constructivism, connectivism. According to progressivism, the professional development of physical education faculty is considered through the prism of individual abilities and their development during the process of active construction of knowledge in a practice-oriented academic environment of a higher education institution. In the context of existentialism, we consider the professional development of physical education faculty as a toolkit for the development of the personality. The ideas of constructivism are extrapolated to the professional development, since the latter provides opportunities for the active construction of a knowledge system, based on the study of the peculiarities of the professional sphere, the identification of regularities in its development, organization and functioning, which allow predicting the results of professional activity. According to cognitivism professional development is a complex process that requires cognitive and emotional participation in individual and collective format, the ability and desire to find out one’s own place in terms of beliefs and principles, as well as familiarization and implementation of innovations in practice. From the perspective of connectivism, we consider the professional development of physical education faculty as many opportunities for obtaining information, processing it, distinguishing its most important elements, realizing the connections between various sources and the content of information with the aim of their further use for personal and professional growth by using modern information and communication technologies.